Transport accident mortality in Chile: trends from 2000 to 2012 - Otzen, Tamara (2016)
The aim of this study is to describe the trends of transport accident mortality in Chile from 2000 to 2012 by year, geographic distribution, gender, age group, and type of accident. Population-based study. Data for transport accident mortality in Chile between 2000 and 2012 were used. The crude and adjusted per region transport accident mortality rates were calculated per 100,000 inhabitants. The annual percentage change (APC) of the rates and relative risks (RR) were calculated. The average transport accident mortality rate (TAMR) in Chile (2000-2012) was 12.2. The rates were greater in men (19.7) than in women (4.8), with a RR of 4.1. The rates were higher in the country's southern zone (15.9), increasing in recent years in the southern zone, with a significant positive APC in the northern and central zones. The Maule region had the highest rate (21.1), although Coquimbo was the region with the most significant APC (2.2%). The highest rate (20.3) was verified in the 25-40 age group. The highest rate (14.3) was recorded in 2008. The most frequent type of accident was pedestrian. In general the APC trends of the rates are increasing significantly. This, added to rapid annual automotive growth, will only exacerbate mortality due to transport accidents.